EVALUATING THE EFFECTIVENESS OF PORTFOLIO OF THE MUTUAL FUND MANAGEMENT - Alla V. Trofimovskaya; Anna A. Vershinina; Maksim V. Fatin (Статистика и экономика, 2016)
The article deals with the problem ofevaluating the effectiveness of portfolio of mutual fund management.